2020
DOI: 10.21715/gb2358-2812.2020342161
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical background - what a complex meaning has such a simple expression!

Abstract: The term background was introduced in geochemistry applied to the prospecting of mineral deposits to designate a value, below which the samples would represent normal contents and above which they would be deviations from normality and could represent anomalies related to mineral deposits. In the 1980’s, when the techniques applied in mineral exploration were absorbed by the nascent environmental sciences, the term background was also incorporated with a very similar meaning. However, since its first applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Medians and 90th percentiles of element concentrations are considered as robust parameters for geochemical distributions (Licht 2020). However, the scope of this study is limited to a regional scale; this is due to a small number of samples (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Medians and 90th percentiles of element concentrations are considered as robust parameters for geochemical distributions (Licht 2020). However, the scope of this study is limited to a regional scale; this is due to a small number of samples (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies showed clearly geochemical spots of As, Cu, Ni, Pb and V varying from 0.01 or 0.1 ppm to some hundreds or thousands of ppm considering continental, national or local scales and the complexity associated to different aspects of geochemical prospecting. Licht (2020) remarked the diversity associated to sampling media, granulometry, solubilization, analytical methods and data processing methods in the perspective of geochemical background. Geochemistry of stream sediments and soils from Vale do Ribeira, Sao Paulo state, Brazil, were compared (FILIPPINI-ALBA et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In general, soils have a strong correlation to the parent geological material. In contrast, stream sediment samples have a wider representativeness, restricted to the whole upstream catchment area of the sampling point, and high susceptibility, not only due to the different lithologies occurring in the catchment area, but also due to changes in the hydrosedimentological dynamics, influenced by local seasonal variations, and changes in land cover and land use [15,16].…”
Section: Introductionmentioning
confidence: 99%